Dynamic Spillover and Market Integration between Global Commodities and Pakistan Stock Exchange (PSX) amid COVID-19 and the Russia-Ukraine War - Muhammad Maaz; Dr. Sajjad Ahmad Khan; Dr. Amir Hussain (Dialogue Social Science Review (DSSR), 2025)
The study fills a critical research gap in the literature by examining the dynamic interlinkages and volatility spillovers between Pakistan’s financial market and major international commodities during periods of global crisis, specifically the COVID-19 pandemic and the Russia-Ukraine conflict. Unlike previous studies focused on developed or larger emerging markets, this research centers on Pakistan—a frontier economy with unique vulnerabilities. Using the ARMA-GARCH model, the study effectively captures the mean and volatility dynamics of the MSCI Pakistan Index (MSCI_PAK) and key commodities such as gold, oil, soybean oil, wheat, corn, and rice. This framework is well-suited to model the volatility clustering and time-varying shocks characteristic of crisis periods. The results reveal generally weak return correlations between MSCI_PAK and the selected commodities, suggesting distinct market drivers and opportunities for portfolio diversification. However, strong volatility persistence is observed, particularly in gold and oil, with oil showing quicker mean reversion. Agricultural commodities exhibit prolonged volatility, signaling their sensitivity to sustained external shocks. High GARCH coefficients for soybean oil and wheat indicate lasting volatility spillovers, and extreme kurtosis in rice and corn points to vulnerability to abrupt crisis-induced price shocks. During the COVID-19 pandemic, gold acted as a safe-haven asset with a negative correlation to MSCI_PAK, while oil and agricultural commodities showed weak relationships. Similarly, during the Russia-Ukraine conflict, widespread volatility clustering persisted, with gold and oil remaining volatile and agricultural commodities showing moderate negative correlations to Pakistan’s market. In conclusion, the study finds that while return linkages between Pakistan’s financial market and global commodities are limited, volatility transmission is significant and persistent. These insights are crucial for investors and policymakers aiming to build resilient portfolios and develop effective risk management strategies in the face of global shocks.